A Theory-Based, Technology-Assisted Intervention in a Hybrid Cardiac Rehabilitation Program for Patients with Coronary Heart Disease: A Feasibility Study - Mei Sin Chong; Janet Wing Hung Sit; Kai Chow Choi; Anwar Suhaimi; Sek Ying Chair (Elsevier, 2023)
Summary: Purpose: To assess the feasibility of a technology-assisted intervention in a hybrid cardiac rehabilitation program among patients with coronary heart disease. Methods: This study was a two-arm parallel randomized controlled trial. Twenty-eight patients with coronary heart disease were randomly assigned to either the intervention group, receiving a 12-week technology-assisted intervention (n = 14), or the control group (n = 14), receiving usual care. Guided by the Health Belief Model, the intervention group received three center-based, supervised exercise training sessions, a fitness watch that served as a cue to action, six educational videos, and a weekly video call. The Self-efficacy for Exercise, exercise capacity, and Health Promoting Lifestyle Profile II were assessed at baseline and immediately post-intervention (12-weeks). Results: Among the 28 patients who participated in this study, 85.7% completed the program, with a relatively low attrition rate (14.3%). The number of exercise training sessions accomplished by the participants in the intervention group was 51.27 ± 19.41 out of 60 sessions (85.5%) compared to 36.46 ± 23.05 (60.8%) in the control group. No cardiac adverse events or hospitalizations were reported throughout the study. Participants in the intervention group showed greater improvement in health-promoting behaviors when compared with the control group at 12 weeks. Within-group effects demonstrated improvement in exercise self-efficacy and exercise capacity among participants in the intervention group. A participant satisfaction survey conducted immediately post-intervention revealed that participants were "very satisfied" (23.1%) and "satisfied" (76.9%) with the technology-assisted intervention. Conclusions: The findings demonstrated that technology-assisted intervention in a hybrid cardiac rehabilitation program was feasible and suggested to be beneficial in improving exercise self-efficacy, exercise capacity, and health promoting behavior among patients with coronary heart disease. A full-scale study is needed to determine its effectiveness in the long term. Trial and protocol registration: ClinicalTrials.gov NCT04862351.https://clinicaltrials.gov/ct2/show/NCT04862351.